2020
DOI: 10.1126/sciadv.aaz0478
|View full text |Cite
|
Sign up to set email alerts
|

The plant cuticle regulates apoplastic transport of salicylic acid during systemic acquired resistance

Abstract: The plant cuticle is often considered a passive barrier from the environment. We show that the cuticle regulates active transport of the defense hormone salicylic acid (SA). SA, an important regulator of systemic acquired resistance (SAR), is preferentially transported from pathogen-infected to uninfected parts via the apoplast. Apoplastic accumulation of SA, which precedes its accumulation in the cytosol, is driven by the pH gradient and deprotonation of SA. In cuticle-defective mutants, increased transpirati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 55 publications
(104 reference statements)
2
53
0
Order By: Relevance
“…Here, the authors showed that SAG was hydrolyzed in the apoplast to SA and that rather SA than SAG entered the cell. In addition, other studies support our notion that both NHP and SA are mobile between local and systemic tissue in Arabidopsis and tobacco (Yalpani et al, 1991;Chen et al, 2018;Lim et al, 2020). Nevertheless, it is still a matter of debate, as there was also evidence presented that SA is not the mobile signal for SAR (Vernooij et al, 1994b;Vernooij et al, 1994a).…”
Section: Discussionsupporting
confidence: 75%
“…Here, the authors showed that SAG was hydrolyzed in the apoplast to SA and that rather SA than SAG entered the cell. In addition, other studies support our notion that both NHP and SA are mobile between local and systemic tissue in Arabidopsis and tobacco (Yalpani et al, 1991;Chen et al, 2018;Lim et al, 2020). Nevertheless, it is still a matter of debate, as there was also evidence presented that SA is not the mobile signal for SAR (Vernooij et al, 1994b;Vernooij et al, 1994a).…”
Section: Discussionsupporting
confidence: 75%
“…Similarly, cuticle‐defective Arabidopsis mutants, which display impaired apoplastic SA accumulation and transport, accumulate SAR signals in petiole exudates of infected leaves, but do not respond with SAR to petiole exudates of infected wild‐type plants (Fig. 1) (Xia et al ., 2009; Lim et al ., 2020). Notably, Lim et al .…”
Section: Systemic Acquired Resistance (Sar)mentioning
confidence: 99%
“…et al (1994);Lim et al (2020) C. Wenig et al(2019) Jung et al (2009); Gao et al (2014); Lim et al (2016); Wenig et al (2019) Park et al (2007, 2009) Y. Wang et al (2018); Wenig et al (2019) Riedlmeier et al (2017);Wenig et al (2019) Chanda et al (2011); Wenig et al (2019) Jung et al (2009); Cecchini et al (2015) Maldonado et al Signaling functions of systemic acquired resistance (SAR) signaling components in local SAR signal generation/transmission and systemic SAR signal perception/propagation. Signaling components are listed in groups of potentially co-operating signals and assigned to phloem-mediated (green arrow) and airborne (pink arrow) routes.…”
mentioning
confidence: 98%
“…In contrast, two other SAR-associated chemical signals, glycerol-3-phosphate (G3P) and azelaic acid (AzA), are transported preferentially via plasmodesmata (Lim et al, 2016). More interestingly, Lim et al (2020) recently showed that transport of SA from local to distal tissues is essential for SAR, and the transportation is governed by water potential in the infected tissue (Figure 1). Indeed, reduced water potential preferentially routes SA to cuticle wax rather than to the apoplast in cuticle-defective mutants (Lim et al, 2020).…”
Section: Transportation and Function Of Sa In Sarmentioning
confidence: 99%